2003
DOI: 10.2337/diacare.26.6.1825
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Midthigh Low- Density Muscle and Insulin Resistance in Obese Nondiabetic Patients in Korea

Abstract: OBJECTIVE -We investigated the link between lipid-rich skeletal muscle, namely lowdensity muscle, and insulin resistance in Korea.RESEARCH DESIGN AND METHODS -Abdominal adipose tissue areas and midthigh skeletal muscle areas of 75 obese nondiabetic subjects (23 men, 52 women; mean age Ϯ SD, 41.9 Ϯ 14.1 years) were measured by computed tomography (CT). The midthigh skeletal muscle areas were subdivided into low-density muscle (0 to ϩ30 Hounsfield units) and normal-density muscle (ϩ31 to ϩ100 Hounsfield units). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 32 publications
6
32
0
2
Order By: Relevance
“…Kim et al [23] reported a significant correlation between the low density muscle mass of the femoral quadriceps muscle and insulin resistance in obese subjects, which was consistent with reports from a similar study. The authors of the present study recommend additional research on insulin resistance and femoral quadriceps muscle increase in Korean diabetes patients.…”
Section: Discussionsupporting
confidence: 84%
“…Kim et al [23] reported a significant correlation between the low density muscle mass of the femoral quadriceps muscle and insulin resistance in obese subjects, which was consistent with reports from a similar study. The authors of the present study recommend additional research on insulin resistance and femoral quadriceps muscle increase in Korean diabetes patients.…”
Section: Discussionsupporting
confidence: 84%
“…Low‐density muscle represents lipid‐rich skeletal muscle, which includes fat components both between and within the muscle fibers. A number of previous studies have shown that low‐density muscle is significantly related to insulin resistance in obese type 2 diabetic patients (20, 41).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that fat in these areas was significantly related to insulin resistance. [21, 33, 34] Although fat infiltrated in muscle accounts for a relatively small portion of the total skeletal muscle, it may be important in the development of type 2 diabetes apart from loss of muscle mass. [34, 35] We also did not consider muscle quality, such as muscle strength, or other muscle characteristics.…”
Section: Discussionmentioning
confidence: 99%